Auditoría ambiental de las actividades de mantenimiento aeronaútico y su relación con la contaminación ambiental conforme a la normativa ISO 14001 en la Dirección de la Industria Aeronaútica del Ecuador (DIAF-CEMA). Latacunga 2015. Diseño de sistema de gestión ambiental. - Romero Andrade, Michael David (2015)
The Aeronautic Industry Department of Ecuador “DIAF-CEMA” is a public entity, assigned ECUADORIAN AIR FORCE, which offers maintenance services of civil and military services. In face to limited environmental operative viability is focused in the need to implementing strategies, which let to increase its environmental viability through the environmental aspects and impacts management generated by the aeronautic maintenance activities to accomplish with Ecuadorian currently regulation and show the compromise to have a responsible environment. In this way, an environmental auditory was made to know the actual situation of the organization establishing that exist 9 organizational processes with 25 management activities and 47 environmental impacts of which 61,7 % are related to lower level impacts, 29,78 % are related to intermediate level and 8,51 % upper level to take actions to its control and reduction, by this way establishing the initial point to design the environmental management system appliance to the institution like an active corporative politic through to comply the documented procedures in according with international standard ISO 1400 that dynamic and involve the active participation of the people of the organization to reduce the environmental pollution improving the quality life of the population.